The effect of oil price shocks on asset markets: Evidence from oil inventory news - Ron Alquist; Reinhard Ellwanger; Jianjian Jin (Bank of Canada, 2020)
We quantify the reaction of U.S. equity, bond futures, and exchange rate returns to oil price shocks driven by oil inventory news. Across most sectors, equity prices decrease in response to higher oil prices before the 2007/08 crisis but increase after it. Positive oil price shocks cause a depreciation of the U.S. dollar against a broad range of currencies but have only a modest effect on bond futures returns. The evidence suggests that changes in risk premia help to explain the time-varying effect of oil price shocks on U.S. equity returns.
Keywords: D83; E44; G14; G15; Q41; Q43; 330; Financial markets; Recent economic and financial developments